Necrotizing Pneumonia Causing Noniatrogenic Arterial Air Embolism Resulting in Acute Ischemic Stroke: A Case Report - Brandon Layton; James Walker; William Krogman (Annals of Internal Medicine: Clinical Cases)
A 65-year-old man with necrotizing pneumonia experienced acute neurologic changes immediately after some violent coughing. Computed tomography of the head showed bilateral gas emboli, which correlated with watershed, parasagittal cerebral infarcts noted on magnetic resonance imaging of the brain. Common etiologies of gas-embolic stroke were discarded. As a result of delayed recognition of the gas emboli, the patient did not receive hyperbaric oxygen therapy. Nevertheless, he did improve neurologically and was discharged to a rehabilitation facility. Gas-embolic stroke should be included in the differential when acute neurologic symptoms are observed in patients with necrotizing pneumonia accompanied by severe cough.